Phraseological Units in Newspapers Headlines on the Ukrainian Crisis - Rabrenović, Milica L. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
The present paper provides the usage of phraseological units in newspaper headlines during the Ukrainian crisis which are analyzed with the aim of examining how idioms in media headlines impact the overall message being conveyed and its interpretation by recipients. The corpus consists of newspaper headlines collected from various online portals (rts.rs, blic.rs, nova.rs, rs.n1info.rs, informer.rs, politika.rs). We selected ideologically diverse media sources to examine how different media outlets inform about the same events. As control sources for this research, we used the Dictionary of Serbo-Croatian Literary and Folk Language of the Serbian Academy of Sciences and Arts, the Dictionary of the Serbian Language of the Matica Srpska, Josip Matešić’s Phraseological Dictionary of Croatian or Serbian Language, and Đorđe Otašević’s Phraseological Dictionary of the Serbian Language. The identified phraseological units were semantically classified and analyzed based on their expressive value, and then interpreted from the perspective of critical discourse analysis.